Kepatuhan Masyarakat Wajib Pajak Dalam Membayar Pajak Bumi dan Bangunan di Kelurahan Maesa Unima Kecamatan Tondano Selatan Kabupaten Minahasa - Cantika Suryani; Thelma Wawointana; Devie Siwij; ismi dini saefa (Post Graduate School of Government Science, 2023)
This paper describes community compliance in paying land and building tax payers in the Maesa Unima sub-district, Tondano Selatan District, Minahasa Regency. The compliance of the taxpayer community is very important in planning the plans that have been planned, with compliance making a plan run smoothly. With the decrease in the realization of taxes that have been set, it proves that many taxpayers are still not fulfilling their obligations in paying taxes for the creation of the prosperity of a country. This study aims to find out what are the reasons for non-compliant taxpayers in paying land and building tax and the level of land and building tax revenue in Maesa Unima Village, South Tondano District, Minahasa Regency. This research method uses qualitative methods. The results of this study as well as some information from informants note that the low compliance of the tax payer community in the Maesa Unima Village is triggered by inadequate infrastructure limitations, as well as limited community data and limited workforce, and tax subjects do not occupy tax objects.